Enhancing the performance of foam concrete containing fly ash and steel slag via a pressure foaming process. (20th December 2021) - Zhou, Dongdong; Gao, Hongyu; Liao, Hongqiang; Fang, Li; Cheng, Fangqin
Abstract: Obtaining foam concrete with a high strength/density ratio via the current foaming under atmospheric conditions (FAC) is difficult. We independently developed a pressure foaming device, realizing the preparation of foam concrete with a high strength/density ratio (7.6 MPa/(g·cm −3 )). We systematically compared the cross sections, pore size distributions, pore wall thicknesses, porosities of blocks prepared via FAC and pressure foaming process (PFP) using X-ray computed tomography. Results show that the pore size distribution of the block obtained via FAC is prone to polarization, i.e., it develops in both the direction of smaller pore volume and larger pore volume simultaneously. The pore shape of the concrete obtained via the PFP is closer to spherical than that obtained via FAC. The proportion of pores with sizes of 150–800 μm in the PFP concrete reaches 77.5%, 1.3 times the proportion of such pores in the FAC concrete. The mechanism of strengthening the performance of foam concrete obtained via the PFP is also discussed. PFP improves the uneven force of the bubbles in the foam concrete, promotes the force balance of the bubbles, and improves the uniformity of the pore structure by applying pressure during the foaming process. Such foam concrete is essential for thermal-insulating and load-bearing prefabricated composite wall applications. Graphical abstract: Image 1